2014
DOI: 10.1007/s00436-014-3957-y
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic effect of wild rue (Peganum harmala L.) against experimentally induced coccidiosis in broiler chicks

Abstract: Organic farming of poultry has increased in recent years as the prophylactic use of antibiotics has come into disfavor. This study was conducted to explore the antiparasitic effect of a methanolic extract of Peganum harmala in broilers challenged with coccidiosis. For this purpose, 200 1-week-old broiler chicks were divided into five treatments: negative control (basal diet, Ph-0/NC), positive control (basal diet with coccidiosis challenge, Ph-0/C), and three groups challenged with coccidiosis and supplemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 19 publications
2
32
0
Order By: Relevance
“…Coccidiosis is one of the major protozoan diseases of poultry caused by genus Emeria. This organism mostly affects the gastrointestinal tract causing reduced feed intake, weight gain, worsen feed efficiency and higher mortality (Tanweer et al 2014;Chand et al 2016). Massive economic losses are associated with the outbreak of coccidiosis in the form of morbidity and mortality of the birds (Abudabos et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coccidiosis is one of the major protozoan diseases of poultry caused by genus Emeria. This organism mostly affects the gastrointestinal tract causing reduced feed intake, weight gain, worsen feed efficiency and higher mortality (Tanweer et al 2014;Chand et al 2016). Massive economic losses are associated with the outbreak of coccidiosis in the form of morbidity and mortality of the birds (Abudabos et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Eimeria species mostly infect the ceca and small intestines. During caecal coccidiosis, different types of lesions are present which depend upon the species of coccidia (Tanweer et al 2014). The organisms proliferate in the intestinal cells and cause tissue destruction (Arczewska et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of induction of atherogenesis has been shown to be as a result of the accumulation of oxidized lipids within the artery wall. High plasma level of cholesterol, LDL cholesterol in particular, is one of the prominent risk factors for atherosclerosis and thus cardiovascular diseases [23]. Medicinal plants and their derivatives are promisingly gaining wide usage worldwide as they are a potential source of bioactive agents used as pharmaceuticals [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research was carried out on the chemical composition which revealed that β ‐carboline and quinazoline alkaloids are important ingredients accounting for many pharmacological and therapeutic effects, such as analgesic , antibacterial , antiparasitic activity , strong reversible inhibition activity of monoamine oxidase , and cytotoxic activities, etc . [7 – 9].…”
Section: Introductionmentioning
confidence: 99%